Hydrochemical process and controls on the hydrochemistry of river water in the Muling-Xingkai Plain, Northeast China - Su, Chen; Liu, Yuan; Cheng, Zhongshuang; Wang, Wenzhong; Zheng, Zhaoxian (Frontiers in Environmental Science, 2022)
River waters are an important supply sources for the agricultural production in the Muling-Xingkai Plain (MXP), northeast China, and the hydrochemical processes and chemical compositions of river water have changed due to the influences of human activities. However, knowledge about nature factors and human influences on water quality of river waters is still unclear, which has important constrains on agricultural irrigation management and food security. In this study, a total of 33 samples from rivers in the MXP were collected to determine the key factors affecting the chemical compositions and hydrochemical evolution processes of river waters. The water types of Abuqin River (AR), Qihulin River (QR) and Muling River (MR) were Ca·Mg-HCO3, Ca·Mg-HCO3, and Ca·Mg-HCO3·Cl, respectively. Principal component analysis (PCA) and hydrochemical analysis showed the natural sources of chemical ions in river waters are silicate and carbonate minerals. The chemical fertilizers only slightly influence the chemical compositions of river waters due to the retardation of black soil with weak permeability. The chemical compositions of river waters in MR are influenced significantly by domestic sewage compared with other two rivers. At present, human activities only play a limited roles in determine the river quality, and the contents of major chemical ions in river waters meet the irrigation standard. Although the irrigation with river waters do not lead to the food safety issue, the government agencies should adopt adequate measures to control the indiscriminate discharge of domestic sewage and indiscriminate application of fertilizers for preventing the accumulation of pollutants in river waters. This study is beneficial to the sustainable development of agricultural production in the MXP.